Community empowerment for health service integration in disaster-prone rural Indonesia: a multidisciplinary literature review - Yanni, Daffa Arkananta Putra (Journal of Community Empowerment for Health, 2026)
Introduction: Indonesia, one of the most disaster-prone countries globally, faces persistent challenges in delivering equitable and resilient health services, particularly in rural regions vulnerable to natural hazards. Community empowerment has emerged as a promising approach to strengthening health systems by fostering local capacity, promoting inclusive participation, and ensuring culturally appropriate interventions. However, the integration of community empowerment into health service frameworks in disaster-prone rural areas remains fragmented and inconsistent. This literature review aims to explore how community empowerment contributes to the integration of health services in disaster-prone rural areas of Indonesia.Methods: This study employed a narrative synthesis approach to analyze peer-reviewed articles published between 2020 and 2025. Articles were selected from electronic databases including PubMed, ScienceDirect, and Google Scholar using specific keywords related to community empowerment, health services, disaster contexts, and rural Indonesia. From an initial pool of 230 studies, fifteen articles were included for in-depth thematic analysis.Results: The findings reveal that community empowerment facilitates improved health service delivery, enhanced disaster preparedness, and greater resilience through strategies such as participatory planning, utilization of local knowledge, social capital mobilization, and grassroots leadership. However, these initiatives often face significant challenges, including short-term funding, exclusion of marginalized groups, and limited institutional support.Conclusion: The review concludes that community empowerment has shown effectiveness in integrating health services in disaster-prone rural Indonesia; its sustainability and scalability require stronger policy support, long-term funding mechanisms, and inclusive program design. Future efforts must prioritize co-created approaches that align with the socio-cultural and structural realities of rural communities to achieve meaningful and lasting health outcomes.